Access to technology and foundational math proficiency among students: empirical evidence from India - Prashant Poddar; Valentina Rotondi; Ridhi Kashyap (Humanities & Social Sciences Communications)
Abstract Digital resources such as laptops have the potential to improve access to educational resources and provide personalized and uninterrupted learning opportunities for students. The impacts of these technologies may be especially salient in contexts where classroom sizes are large and schooling quality is poor. Here, we study the impacts of access to laptops on foundational math proficiency in one such context, i.e., India, exploiting plausibly exogenous variation in the implementation of the Tamil Nadu Free Laptop Scheme (TFLS). Introduced in 2011, the TFLS was one of the largest and targeted free laptop programs in the world, distributing over 5 million laptops. Using data from the Annual Status of Education Report (ASER) and India Human Development Survey (IHDS) within a double difference design, we show positive effects of access to laptops on foundational math proficiency of students, with the largest improvements experienced by those in economically disadvantaged households. We further find that these positive effects on foundational math proficiency are complemented by improvements in other education-related outcomes of students, such as more time spent on learning, better comprehension of language, and a reduction in private tuition. We provide evidence that laptops are able to close economic and gender divides in education. Our results remain robust to a variety of falsification and sensitivity checks.